How good antioxidant is the red wine? Comparison of some in vitro and in vivo methods to assess the antioxidant capacity of Argentinean red wines - Baroni, María Verónica (2012)
There are many reports on the wine composition and their biological activities. However, to our knowledge, there are no reports linking chemical composition and the protective effect from oxidative stress on Saccharomyces cerevisiae. Our main goal was assessing the antioxidant capacity (AC) of three Argentinean red wines (Cabernet Sauvignon, Malbec and Syrah) and its correlation with polyphenols content (TP) and the phenolic profile. In vitro AC was measured by TEAC and FRAP assays, while in vivo AC was measured using the eukaryote model S. cerevisiae exposed to H2O2 to induce oxidative stress. Three wine varieties showed significant AC both in vitro and in vivo. Furthermore, we observed some protective effects of wine in cells exposed to H2O2, which was correlated to the increased activity of antioxidant enzymes Glutathione peroxidase (GPx) and Glutathione reductase (GR). Cabernet Sauvignon showed higher AC than other varieties. We did not observe significant correlation between TP content with AC, measured neither in vitro nor in vivo. Conversely, canonical correlation and multiple regression analyses showed that AC is highly correlated to their polyphenolic profile, with significant contribution of kaempferol and catechin. So far, our current results point out the importance of analyzing the entire polyphenolic profile instead of TP in addition to the use of in vivo assays to help understanding differences in AC of wines, which should be extensive to other food products.